Care in place: A case study of assembling a carescape. Issue 8 (31st August 2016) - Ivanova, Dara; Wallenburg, Iris; Bal, Roland
Abstract: In this article we analyse the process of the multiple ways place and care shape each other and are co‐produced and co‐functioning. The resulting emerging assemblage of this co‐constituent process we call a carescape. Focusing on a case study of a nursing home on a Dutch island, we use place as a theoretical construct for analysing how current changes in healthcare governance interact with mundane practices of care. In order to make the patterns of care in our case explicit, we use actor‐network theory (ANT) sensibilities and especially the concept of assemblage. Our goal is to show – by zooming in on a particular case – how to study the co‐constituent processes of place‐ and care‐shaping, revealing the ontological diversity of place and care. Through this, we contribute a perspective of the heterogeneity and multiplicity of care in its dynamic relationship of co‐production with place.